Contamination of engine oils during winter vehicle operation - S. V. Korneev; S. V. Pashukevich; V. D. Bakulina; N. G. Pevnev (Вестник СибАДИ, 2022)
Introduction. The reliability and service life of an engine is largely dependent on the quality of the engine oil. Without oil at the proper level of performance, an internal combustion engine can suffer from wear and tear, which in many cases can lead to engine failure. One of the factors in the loss of the quality level of engine oil is its contamination. For example, kinematic viscosity will gradually increase as the engine oil becomes contaminated with soot, dirt and sludge; or it may be oxidized. If the viscosity of the engine oil is too high, the engine must do extra work to overcome the increased viscosity resistance.Fuel and water dilution is one of the most common contaminants in diesel engines.Materials and Methods. The paper presents the results of a study of the combined effect of water and diesel fuel on synthetic engine oil at their various concentrations. The influence evaluation of contaminants on changes in the performance characteristics of the lubricant, such as: kinematic viscosity at 40° C (measurement was carried out on an automatic Stabinger SVM 3000 viscometer), base and acid numbers (values obtained using an automatic Titroline Alpha 20 Plus titrator), as well as concentration measurement elements - indicators of engine oil on an optical emission spectrometer with inductively coupled plasma of the iCAP 7000 series.Conclusions. The presence of contaminants in the engine oil leads to an increase in kinematic viscosity, during the operation of the engine oil, the value of its base number becomes less, and the value of the acid, on the contrary, increases. It is necessary to replace engine oils when the base number decreases by 50% or according to the balance of base and acid numbers.Scope of Study/Opportunity. This type of low temperature performance modelling provides insight into how the oil deteriorates and evaluates the change in oil performance during use.Originality/value. The study can be the basis for developing recommendations for improving the maintenance of internal combustion engines for enterprises that have cars with diesel engines at their disposal in order to increase the resource of power units and reduce operating costs.